PENTINGNYA POLA ASUH ORANG TUA DALAM PEMBENTUKAN KEPRIBADIAN ANAK - Yuni S.P. Lumbantoruan; Redita Manullang; Betris S. Simbolon; Abdel Jesika Lase; Melani Napitupulu; Dorlan Naibaho (CV. Denasya Smart Publisher, 2024)
Parents are the first place children get education. A child's personality will be formed from the family, namely early on. Parenting patterns from parents play an important role in the development of children's personality. This study aims to describe how the important role of parenting patterns in the development of children. The subjects of this study were children from BUKIT CAHAYA HIGH SCHOOL and DAIRI SWASTA TEKNIK SMK. The method used is qualitative method with descriptive approach. Data obtained from the results of interviews with subjects. The results of this study indicate that children who do not get good parenting from parents greatly affect the development of the child's personality. In this study, it is very clear that good parenting will form a good personality in the child if the parenting is not good, it will form a child's personality that is not good either. So, parents are required to provide good parenting